The interrelation between lipid profile in chronic HCV patients and their response to antiviral agents. (2nd January 2021) - Eletreby, Rasha; Anees, Mahmoud; Naguib, Mariam; Kobtan, Abdelrahman; Helmy, Amal; Khalaf, Nahla; Mansour, Shimaa; Hassany, Mohamed; El Akel, Wafaa; Hashem, Ahmed; Doss, Wahid; Esmat, Gamal
ABSTRACT: Objectives: This study aims to assess the changes of lipid profile in chronic HCV patients; before, during, and after treatment with DAAs and their association with treatment response. Methods: 301 chronic HCV patients who received SOF-based therapy were included. Serum lipid profile was assessed at different check points; baseline, 6 weeks on treatment, end of treatment (EOT) and 12 weeks after EOT; and compared between SVR and non-SVR groups. Results: SVR group had significantly higher baseline lipid parameters compared to non-SVR group with significant increase in lipid parameters at different time points apart from HDL-C. Non-SVR group showed non-significant change in lipid parameters apart from LDL-C. On week6 on treatment, cholesterol level > 125 mg/dl was 92.8% sensitive, 97.3% specific with 95.5% NPV, and AUC of 0.989 in prediction of SVR. Similarly, LDL > 57 mg/dl was 83.7% sensitive, 100% specific with 93.3%, NPV and AUC of 0.952. Baseline cholesterol and LDL were significantly associated with SVR. Conclusion: Higher baseline lipid parameters and their further elevation starting from week 6 on treatment are good predictors of SVR in HCV patients. Successful HCV therapy with DAAs is associated with a significant increase in lipid parameters.